World Bank Reference Guide to Climate Change Framework Legislation - World Bank (World Bank, Washington, DC, 2021)
Climate change is a grave threat to global development and shared prosperity. Its impacts are expected to intensify even as the world responds to the Coronavirus (COVID-19) crisis. The poor and most vulnerable will be the worst affected. Climate change poses particularly difficult challenges for policy makers. It demands action across all sectors of the economy and across all of society. Action to address climate change requires coordination among multiple governmental and nongovernmental stakeholders. The extended time frame over which climate change unfolds requires a capability to plan, implement, and sustain a credible commitment to increasingly ambitious policies over multiple political cycles. To address these challenges, countries need effective institutions. National framework legislation on climate change can help put these institutions in place. It can enshrine stable and ambitious targets, create mechanisms for realizing these targets, and ensure proper oversight and accountability. The authors hope the twelve key principles for framework legislation laid out in this guide will contribute to building back better by helping countries to lay a solid foundation for climate-smart development that creates new jobs and markets, boosts economic growth, and provides a safer, cleaner environment for all.